MENAKAR KEBIJAKAN FULL DAY SCHOOL (Studi Analisis Permendikbud No 23 Tahun 2017) - Muhammad Miftah (Jurnal Perspektif)
The full day school policy stipulated in the regulation of Education and Culture Minister (Permendikbud) Number 23 of 2017 makes the anxiety for the education activists who are not ready for the consequences of this regulation. The anxiety of these educational activists began to disappear when Permendikbud No. 23 of 2017 was abolished by a higher regulation, namely Presidential Regulation (Perpres) No. 87 of 2017 which asserted that the five-day school is an option rather than an obligation. In this Presidential Decree, there is a gap for educational institutions to run the school hours in accordance with Permendikbud No. 23 of 2017. It becomes interesting to be investigated in the realm of educational policy. This study analyzes how the emergence of a policy in education, how to implement and evaluate the policies that have been applied especially Permendikbud No 23 of 2017 about school hours, because there are still schools and madrasah that use school hours in accordance with this permendikbud.